2021
DOI: 10.1021/acs.jmedchem.0c01399
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Internalization and Inhibition Capacity of New Anti-Glioma Peptide Conjugates: Physicochemical Characterization and Evaluation on Various Monolayer- and 3D-Spheroid-Based in Vitro Platforms

Abstract: Most therapeutic agents used for treating brain malignancies face hindered transport through the blood−brain barrier (BBB) and poor tissue penetration. To overcome these problems, we developed peptide conjugates of conventional and experimental anticancer agents. SynB3 cell-penetrating peptide derivatives were applied that can cross the BBB. Tuftsin derivatives were used to target the neuropilin-1 transport system for selectivity and better tumor penetration. Moreover, SynB3-tuftsin tandem compounds were synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 99 publications
(193 reference statements)
0
24
0
1
Order By: Relevance
“…It is known that fixation of cells may lead to redistribution of peptides, causing them to be localized in the nucleus [64] . However we [65] and others, [66] found that using mild condition for fixation did not alter the internalization pattern of peptides. Thus, fixed cells were used to get a picture about the cellular distribution of peptides.…”
Section: Resultsmentioning
confidence: 58%
“…It is known that fixation of cells may lead to redistribution of peptides, causing them to be localized in the nucleus [64] . However we [65] and others, [66] found that using mild condition for fixation did not alter the internalization pattern of peptides. Thus, fixed cells were used to get a picture about the cellular distribution of peptides.…”
Section: Resultsmentioning
confidence: 58%
“…In this study, we have employed a modified method based on ( 55 ). Briefly, micromolds for casting 3D Petri dishes (MicroTissues, Sigma, 5 × 7 array) were filled with molten agarose (2% ( w / v ) in PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to seeding process, nuclei were stained with Hoechst 33342 solution (0.2 µM) for 30 min (Figure 2). Based on our previous work (55), the nuclear stain could not successfully penetrate into deeper layers of the spheroids (mostly localized at the spheroid surface), and towards the center of the spheroids the Hoechst 33342 signal was gradually decreasing. Stained cells were incubated in 2 ml DMEM CM for 48 h while cell-to-cell adhesion drives the aggregation and formation of spheroids.…”
Section: Ebc-1 Spheroids As Lung Tissue-mimicking Platform To Capture Penetration Profile Of the Cf Peptidesmentioning
confidence: 96%
“…1a). 2,[21][22][23][24][25][26][27] This mechanism allows the TfR to efficiently penetrate tumors and cross the blood-brain barrier to deliver iron to the brain. The attachment of transferrin or ligands of other transcytosis receptors to operational transport systems has been shown to improve delivery into deep tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The attachment of transferrin or ligands of other transcytosis receptors to operational transport systems has been shown to improve delivery into deep tissue. 2,[21][22][23][24][25][26][27] Evidence is emerging that the TfR also participates in thiolmediated uptake [28][29][30][31][32] and viral entry, 28,33,34 including oligonucleotide phosphorothioates 35 and SARS-CoV-2, 28,34 respectively (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%